(untitled) (International Seven Journal of Multidisciplinary, 2023)
The 2008 financial crisis brought huge losses to the global financial market. This article will analyze the financial crisis. This article first outlines the beginning and end of the financial crisis, and points out that the core factor is the outbreak of the subprime mortgage crisis. Afterwards, it will explain and analyze the core financial instruments, such as MBS, CDO, CDS, that appeared in this financial crisis. Then it analyzes the multi-faceted impact of the crisis on China and the United States. The coming examples illustrate the rescue plans of the United States. The U.S. plans are: US Federal Reserve Rate Cut and Emergency Stabilization Act of 2008, Mortgage Loan Adjustment Program and Quantitative easing and Rescue Financial Institutions. Finally, it is concluded that the cause of the financial crisis is the outbreak of the subprime mortgage crisis, which can also be understood as a large number of interests driving financial institutions to deceive the market. And the core of this crisis is credit bankruptcy.